Species Concentration Gradient Method for Solution of Reacting Flow - Ahmad, I.; Ahmad, R.; Tahir, S.; Ahmad, S. (The Nucleus, 2022)
In this article, a new error balance approach utilizing local error per unit step (LEPUS) control strategy has been developed. The error control strategy has been upgraded to incorporate the temporal and spatial discretization error by an adjusting parameter, which has been linked with species gradient present in the chemical mechanism. The accuracy and efficiency of the proposed improved LEPUS (ILEPUS) have been checked by solving the one-dimensional compressible gaseous flow in the absence of a reaction mechanism and compared with the old local error per step (LEPS) and traditional LEPUS strategies. With respect to the concentrations of nitrogen oxide and nitrogen dioxide for the winter season, the simulation predictions have been found to have a positive correlation with the recent experimental data collected in Changchun city, China. For further insights into the scheme, both one- and two-dimensional reacting flows with complex chemical reactions have also been solved using ILEPUS and LEPS, where the ILEPUS scheme has proven better performance as compared with LEPS and LEPUS.